ANALISIS YURIDIS KONTRAK PENGADAAN BARANG SIMULATOR SURAT IZIN MENGEMUDI POLRI - Yulita Heriyanti; Martin Roestamy (Magister Hukum Sekolah Pascasarjana Unida, 2018)
In the case of the procurement of simulators Driving License, there are some deviations made by almost all parties involved to cause state losses. The identification of this research included the implementation of SIM simulators in the Traffic Corps of the National Police, the criminal elements that occurred and their weak points, as well as their positive and negative forms in the implementation of SIM simulator procurement. The research method used in this study is a normative juridical approach using library studies. The results of this study are: 1) There has been a standard agreement between the two parties that is not balanced in the procurement of SIM Simulator goods, where PT. X as the supplier of goods does not get an offer from the formulation of the agreement; 2) In the implementation of SIM Simulator goods procurement, the agreement between the two parties is not balanced and this becomes a weakness that can complicate the position of PT. X because it is in a weak position even though the terms of the agreement made by the National Police Corruption Eradication Agency provide an opportunity for contractors to determine and design contracts as they already are; 3) procurement carried out using the public auction method with third parties is considered effective and efficient in using the budget. But the negative thing is the existence of irregularities committed by partners with unscrupulous officials.